Weather Conditions Associated with the Release and Dispersal of Zymoseptoria tritici Spores in the Argentine Pampas Region - Cordo, Cristina Alicia (2017)
The abundance ofZymoseptoria triticiascospores and conidia in a field was examined throughout two one-year periods (1998-1999 and 1999-2000) establishing the relationship between spore release and weather variables. Radiation, temperature, intensity of rainfall, and relative humidity significantly affected the dispersal of ascospores and pycnidiospores of this pathogen. Spore traps collected both types of spores, at weekly intervals, at two different stages of the wheat crop (vegetative and wheat stubble stages) and different distances from the sources. Ascospores were the predominant sources of inoculum in the field. The numbers of ascospores and pycnidiospores declined with the increase of distance from the sources. The release of pycnidiospores was associated with the increase in rainfall intensity 7 days before the released event and the increase in radiation 60 days before the same event. Relative humidity 3 and 15 days before the release event was positively correlated with ascospores release and negatively correlated with radiation and temperature in all the sampling interval. Also for the first time, a positive correlation between radiation and pycnidiospores dispersal is reported. Understanding the relationship between environment conditions and spores dispersal event could improve the control strategies of the disease.